Nanocarbon-based-ZnO nanocomposites for supercapacitor application - Goswami L.; Kushwaha A.; Goswami S.; Sharma Y.C.; Kim T.; Tripathi K.M. (My University, 2025)
Globally, the demand for clean energy has been cited among the top unprecedented vital issues. The present chapter succinctly reviews the current research advancement of nanocarbon-ZnO nanocomposites for the supercapacitor (SC) applications for addressing energy storage. Today, there is rapid rise in the demand for developing hybrid SCs to overcome the energy density limitations. ZnO has distinctive properties, especially for its potential use as an electrode material in supercapacitors. To advance the application of next-generation SCs, ZnO-based nanostructures have been integrated with diverse types of nanocarbons including carbon nanotubes, activated carbon, biochar, graphene, and carbon nanofibers. This chapter presents a summary of recent progress and developments of ZnO-nanocarbon composite materials, including synthesis techniques and performance enhancement. Further, the chapter concludes with recommendations for future research and challenges. © 2021 Elsevier Inc. All rights reserved.